1985
DOI: 10.1002/actp.1985.010360906
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of structural changes in the process of thermal crystallization of poly(epichlorohydrin) by means of WAXS and microscopic methods

Abstract: Act= Polymerica 36 (1905) Nr. 9 483 Strukturelle Besonderheiten und einige physikalisch-chemische Eigenschaften von aus nichtwaprigen Lcisungen erhaltenen Mischungen oon Cellulose und synthetischen Polymeren. 2. Hochauflcisende 13C-NMR von Mischungen aus Cellulose und synthetischen Polymeren im festen Zustund Mit Hilfe der hochauflosenden 13C-NMR-Spektroskopie wurden Mischungen von Cellulose mit Polymethylmethacrylat, Polyacrylnitril, Polyvinylacetat, Polyvinylalkohol und Polydimethylsiloxan mit unterschiedlic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The racemic monomer is also readily polymerized and generates a large fraction of crystalline, isotactic polymer with long stereoregular sequences. By use of polarized light microscopy, Zmudzinski et al 31 have shown previously that the spherulitic radial growth rates of partially crystalline isotactic poly((R,S)-epichlorohydrin) are sufficiently slow to permit the quantitative measurement over the entire range of temperatures from above the glass transition temperature (Tg) to the melting temperature, with a maximum value in the vicinity of 330 K. The work described in this paper was performed with the aim of developing a better understanding of the crystallization mechanisms which govern the growth of polymer spherulites from the melt through the study of the crystallization kinetics of the optically active forms of poly(epichlorohydrin) and their blends as well as the stereoblock polymer. It was of particular interest to determine the extent to which cocrystallization of polyenantiomers could occur and the effects of polyenantiomer segregation on the rates of crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…The racemic monomer is also readily polymerized and generates a large fraction of crystalline, isotactic polymer with long stereoregular sequences. By use of polarized light microscopy, Zmudzinski et al 31 have shown previously that the spherulitic radial growth rates of partially crystalline isotactic poly((R,S)-epichlorohydrin) are sufficiently slow to permit the quantitative measurement over the entire range of temperatures from above the glass transition temperature (Tg) to the melting temperature, with a maximum value in the vicinity of 330 K. The work described in this paper was performed with the aim of developing a better understanding of the crystallization mechanisms which govern the growth of polymer spherulites from the melt through the study of the crystallization kinetics of the optically active forms of poly(epichlorohydrin) and their blends as well as the stereoblock polymer. It was of particular interest to determine the extent to which cocrystallization of polyenantiomers could occur and the effects of polyenantiomer segregation on the rates of crystallization.…”
Section: Introductionmentioning
confidence: 99%